The Effects of Different Exercise Programs on the Prevention of Perinatal Depression: A Systematic Review and Meta-Analysis - Shu-yuan Mai; Ye Liu; Hao-chong He; Xiao-ying Yan (Clinical and Experimental Obstetrics & Gynecology)
Background: To evaluate the preventive effect of different exercise programs on perinatal depression and to provide practical suggestions to guide the maternal daily exercise plan. Methods: Nine electronic bibliographic databases were searched from inception until 18 January 2022. Meta-analysis of all data was performed using RevMan 5.4. Results: Sixteen RCTs consisting of 2233 maternal cases were included. Compared to women in the control group, women who received exercise effectively prevented maternal perinatal depression (Std. mean difference [SMD] = –1.31, 95% confidence interval [CI] –1.40 to –1.21). Prenatal exercise (SMD = –1.45), aerobic exercise (SMD = –1.78), personal exercise (SMD = –2.03), <30 minutes per single duration (SMD = –1.84), >3 times a week (SMD = –1.91) was the best preventive measure of maternal depression. Conclusions: Exercise can effectively improve the mental health status of perinatal pregnant women, and different exercise start time, exercise content, exercise frequency, exercise form, and single duration of exercise can improve depressive symptoms differently. It is recommended that pregnant women begin from the prenatal period of personal aerobic exercise 3 times a week, each exercise lasting less than 30 minutes, and adjust appropriately according to their own physical conditions.